Circular RNA triple functional domain promotes osteoarthritis' development by modulating the microRNA-136-5p/Nicotinamide phosphoribosyltransferase axis. Issue 3 (1st March 2022) - Yang, Jin; Li, Qi; Wang, Tingting; Lv, Ke
ABSTRACT: Numerous studies have affirmed the participation of circular RNA (circRNA) in osteoarthritis (OA)' development. Previous studies have exposed the elevation of the circRNA triple functional domain (TRIO) in OA, while the molecular mechanism of its effect on OA remains ambiguous. During the study, it was discovered the up-regulation of circTRIO in OA rats and interleukin-1β-treated chondrocytes. Knockdown circTRIO facilitates chondrocyte viability, but suppresses the inflammation, the apoptosis, and matrix metalloproteinases (MMP)-3 and MMP-13 expression, whereas up-regulation aggravates OA. The effect of up-regulation or under-expression of circTRIO on chondrocytes was reversed via the knockdown of Nicotinamide phosphoribosyltransferase (NAMPT) or microRNA (miR)-136-5p separately. Mechanically speaking, circTRIO competitively adsorbing miR-136-5p to target NAMPT influences OA. Briefly, the results of this study inform that the circTRIO/miR-136-5p/NAMPT axis is momentous in OA progression and is supposed to be a promising therapeutic target for some time.